Determining Video Content as a Digital Learning Medium for the Tourism Architecture Course: A Case Study of “MEDIAPAR” - Rizka, Hablana; Rukiati, Enik; Diyah Indartin, Tri Rafika; Diartika, Firda (P3M Politeknik Negeri Jember, 2025)
In the digital era, the development of video-based learning media has emerged as a strategic solution to enhance the quality of education, particularly in the Tourism Architecture course. This article explores the process of designing video content for the “MEDIAPAR” digital learning platform, aimed at improving the comprehension and engagement of students in the Tourism Destination Study Program at Politeknik Negeri Jember. Using a quantitative method through surveys involving students, lecturers, and technicians, the study found that most respondents preferred practical learning content, primarily focusing on tutorials for using SketchUp software. Survey results indicate that 72.9% of students selected this topic as their top priority. Lecturers and technicians also supported the development of visually oriented content to assist students in designing tourism destination masterplans. Therefore, preparing this video content is pedagogically relevant and strategically significant in equipping students to face the increasingly complex challenges of the tourism industry.